Zebrafish Lacking Circadian Gene per2 Exhibit Visual Function Deficiency - Huang, Deng-feng; Wang, Ming-yong; Yin, Wu; Ma, Yu-qian; Wang, Han; Xue, Tian; Ren, Da-long; Hu, Bing (Frontiers in Behavioral Neuroscience, 2018)
The retina has an intrinsic circadian clock, but the importance of this clock for vision is unknown. Zebrafish offer many advantages for studying vertebrate vision and circadian rhythm. Here, we explored the role of zebrafish per2, a light-regulated gene, in visual behavior and the underlying mechanisms. We observed that per2 mutant zebrafish larvae showed decreased contrast sensitivity and visual acuity by optokinetic response assays. By using visual motor response assay, we observed normal OFF responses but abnormal ON responses in mutant zebrafish larvae. Immunofluorescence showed that mutants had a normal morphology of cone photoreceptor cells and retinal organization. However, electron microscopy showed that per2 mutants displayed abnormal and decreased photoreceptor ribbon synapses with arciform density, which resulted in retinal ON pathway defect. We also examined the expression of three cone opsins by quantitative real-time PCR, and the expression of long-wave-sensitive opsin (opn1lw) and short-wave-sensitive opsin (opn1sw) was signiﬁcantly reduced of genotype in mutant zebrafish larvae. Quantitative real-time PCR analyses also showed a down-regulation of the clock genes cry1ba and bmal1b in the adult eye of per2 mutant zebrafish. This study identified a mechanism by which a clock gene affects visual function and defined important roles of per2 in retinal information processing.